Novel SiO2/cellulose nanocomposites obtained by in situ synthesis and via polyelectrolytes assembly - Pinto, Ricardo J. B. (2008)
SiO2/cellulose nanocomposites were prepared using two distinct methodologies: deposition of morphological well-defined SiO2 nanoparticles at the fibres surfaces via polyelectrolytes assembly (layer-by-layer approach, LbL) and the synthesis of SiO2 nanoparticles via tetraethoxysilane (TEOS) hydrolysis in the presence of cellulose fibres. Although both methods were able to produce SiO2/cellulose composites, their final morphological properties strongly depend on the synthetic strategy employed. Whereas in the LbL approach cellulosic fibres covered with discrete spherical SiO2 nanoparticles have been obtained, for the in situ synthesis of SiO2, nanocomposites consisting predominantly on fibres homogeneously coated with a SiO2 film have been obtained. Both methodologies induced a significant decrease in the water uptake capacity of cellulose fibres.